ANALISIS POSTUR KERJA PADA PEKERJA BONGKAR MUAT PADA PT KARYA PRIMA JAYA DI BALIKPAPAN - Mulya, Widya; Zulfikar, Iwan; Maulana , Azwar Aldi (IDENTIFIKASI, 2022)
The purpose of this research is to find out the description of the work posture carried out by workers when loading and unloading at PT Karya Prima Jaya whether it is in accordance with the existing work ergonomics by using a sample of 6 informants. The research tools used to conduct this research are the Ovako Work Analysis System method, Nordic Body Map Questionnaire, observation, and interviews. The results of the analysis obtained are that the work postures carried out by workers at PT Karya Prima Jaya are still not in accordance with the existing work ergonomics because they are often careless or heed the correct work ergonomics when loading and unloading because the workers have not received special training on work ergonomics and resulted in Many musculoskeletal complaints that arise in workers. Based on the Ovako Work Analysis System and the Nordic Body Map, the complaints from workers at PT Karya Prima Jaya vary, namely the back, waist, upper neck, shoulders, upper arms, and legs.